FAKTOR â€“ FAKTOR YANG MEMPENGARUHI DAYA TARIK PRODUK DALAM UPAYA MENINGKATKAN MINAT MEMBELI SEPEDA MOTOR SUZUKI DI KOTA SEMARANG - Naufal, Reza Ahmad; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2015)
This study aims to analyze things that can affect customer purchase intention in Suzukiâ€™s motorcycle in Semarang.Â  This study departs from an existing research problem â€œHow to increase customer purchase intention in Suzukiâ€™s motorcycle?â€. This study was conducted by testing the effect of product quality and brand image variables to the customer purchase intention, where product attractiveness were using as intervening variable in this study.This research method using a technique of sampling purposive with sample as many as 100 respondents who came to Suzuki booth in Semarang. Analysis method in this study used quantitative and qualitative analysis uses multivariate regression analysis with SPSS. The analysis in this study includes: validity and reliability test, classic test assumptions, multivariate regression analysis, hypotheses test through t test and f test, and determination coefficients (r2).The results in the first structure showed that product quality (0.382) and brand image (0.537) has positive and significant effect on the product attractiveness variable, then the result in the second structure showed that product attractiveness (0.852) has a positive and significant effect on the customer purchase intention in Suzukiâ€™s motorcycle. The result on data analysis found adjusted R square point 0.786 from the first structure and 0.724 from the second structure. That means 78.6% of product attractiveness variable explained by product quality and brand image. Meanwhile in the second structure has 77.1% of customer purchase intention explained by product attractiveness. And the rest of them can be explained by other variables outside this research.